A study on the relationship between higher vocational students’ perceived teacher support and learning engagement: The chain mediation of academic self-efficacy and professional commitment - Zhou, Shibing; Wu, Wenchuan (Nurture, 2023)
Purpose: The primary purpose of this study is to analyze the interaction between teacher support and student participation in the learning process. Design/Methodology/Approach: 414 students from vocational colleges participated in this research. The data collected using a reliable and validated questionnaire was made to give an in-depth understanding of how much teachers supported their students’ learning as well as their attitudes towards engagement and learning. Findings: Empirical studies have shown that perceived instructional support has a significant effect on students’ participation in the learning process. Conclusion: Teacher support can not only directly affect students’ learning engagement but also indirectly affect students’ academic self-efficacy and career commitment. Research Limitations: This study may have specific limitations in sample selection methods, types and other aspects. Practical Implications: This study provides guidance and assistance for formulating effective education policies to enhance the level of learning engagement of college students and improve the quality of higher education. Contribution to Literature: The uniqueness of this study is to explore the internal mechanisms and external conditions that promote vocational college students’ learning engagement from the perspective of teacher support.